Ease of Doing Business Index: An Analysis of Investors Practical View - Shakirat Adepeju Babatunde; Mohammed Kayode Ajape; Kabir Dandago Isa; Owolabi Kuye; Eddy Olajide Omolehinwa; Shefiu Abiodun Muritala (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2021)
Abstract: This study investigates the effect of Ease of Doing Business Index (EDBI) on Return on Investment (ROI). The study employs a cross-sectional survey design covering five years from 2015 to 2019. The sample is 47 registered companies with the Lagos Chamber of Commerce and Industry, which is the most representative of the organised private sector group in Nigeria. The study adopts descriptive and linear regression statistical analysis. Findings show a statistically significant negative effect of Government policy continuity. The government procurement process, Raw materials availability and Quality of workforce show adverse effects. Traffic and transportation management, power supply and Security infrastructure show insignificant effect on ROI. Hence, findings indicate that Government procurement process is inimical to ease of doing business in Nigeria despite the government improvement efforts. Since government efforts are insufficient, the World Bank should incorporate private sector ideals into EDBI to create a synergy a robust EDBI. Keywords: Ease of Doing Business, ease of doing business index, return on investment, investors, World Bank. Ease of Doing Business Index: Sebuah Analisis terhadap Pandangan Praktis InvestorAbstrak: Penelitian ini menginvestigasi pengaruh Ease of Doing Business Index (EDBI) terhadap Return on Investment (ROI). Penelitian ini menggunakan desain survei cross-sectional dari tahun 2015 sampai dengan tahun 2019. Sampel penelitian ini adalah 47 perusahaan yang terdaftar di Lagos Chamber of Commerce and Industry. Penelitian ini menggunakan analisis deskriptif dan statistik regresi linear. Dari berbagai elemen EDBI, temuan dari penelitian ini menunjukkan adanya pengaruh negatif yang signifikan antara keterlanjutan kebijakan pemerintah terhadap ROI. Proses pengadaan pemerintah, ketersediaan bahan mentah, dan kualitas tenaga kerja menunjukkan pengaruh berkebalikan dengan ROI. Lalu lintas dan manajemen transportasi, supply listrik, dan infrastruktur keamanan menunjukkan pengaruh tidak signifikan terhadap ROI. Usaha pemerintah dalam meningkatkan proses pengaadaan pemerintah masih belum memadai karena masih kecilnya pengaruh terhadap EDBI Nigeria. World Bank sebaiknya memasukkan pengaruh sektor privat dalam indikator EDBI sebagai upaya menciptakan sinergi antara pemerintah dan sektor privat untuk peningkatan EDBI dan dampaknya pada ekonomi. Kata kunci: Ease of Doing Business, indeks kemudahan berbisnis, pengembalian investasi, investor, Bank Dunia